Modifications Introduced by the Reform of Book VI in Aggravating Circumstances (c. 1326) - Gandía Barber, Juan Damián (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2023)
The reform of Book VI of the CIC has introduced modifications in the aggravating circumstances of the imputability of the crime. After presenting them, working hypotheses are offered exposing possible reasons that explain the reasons why we think they have been carried out. For this, we rely on the criteria that have governed this reform, on the historical circumstances that occurred in the process of Codification of the 1983 Code, and on the canonical doctrine that commented on the 1917 Code.
Keywords: aggravating; mitigating; exonerating; irrelevant; imputability; imputation; crime